FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN INVOLUSIO UTERI PADA IBU NIFAS DI RUMAH BERSALIN WILAYAH KERJA PUSKESMAS RAWASARI TAHUN 2011 - Titik Hindriati (Universitas Batanghari Jambi, 2014)
Uterine involution is the process of the return of the uterus after the baby is born until it reaches the pre- pregnant state . Uterine involution can be observed from the outside by checking the fundus uteri after delivery of the placenta . Within 2-4 hours after delivery , uterine fundus decreased 1 cm ( 1 finger ) every day . Early mobilization has proven successful in reducing thromboembolic events and uterine involusio accelerate the process , then after the first rest period and ended around 2 hours , the mother is expected to perform early mobilization .This study is a descriptive study with cross- sectional design which aims to determine the factors associated with maternal postpartum uterine involusio at the maternity hospital in Puskesmas Rawasari . The population is all postpartum women on the first day up to three with a sample of 44 respondents , sampling techniques accidental sampling . Collecting data using questionnaires tersruktur . Data processed by univariate and bivariate analysis with the chi-square statistical test .The results showed that 34 (77.3 %) of respondents did early mobilization immediately after 2-6 hours postpartum, on the third day involusio occur with decreased uterine fundus height 2 cm below the center of the largest occurred in 16 (36.4%) respondents. Statistical test results showed no significant relationship between early mobilization with uterine involusio with the p-value of 0.000 , there was a significant association between breast-feeding early to involusio uteri with p-value 0.041 and no significant relationship between parity against uterine involusio (p-value 0.355)Based on the above results it can be concluded that on the third day postpartum uterine involusio occur with decreased uterine height of about 2 cm below the center of the next there is a significant association between early mobilization and early breast feeding against uterine involusio, it is expected that the results of this study can be used as a reference in an effort improve the quality of obstetric care services especially early mobilization activities at 2 hours postpartum mothers.Keywords : Early mobilization , and uterine Involusio